Polare maskuliniteter - Hauan, Marit Anne (University of Tromsø, 2012)
In this paper my aim is to read and understand the journal of Gerrit de Veer from the last journey of William Barents to the Arctic Regions in 1596 and the journal of captain Junge on his hunting trip from Tromsø to Svalbard in 1834.It is nearly 240 years between this to voyages. The first journal is known as the earliest report from the arctic era. Gerrit de Veer adds instructive copper engravings to his text and give us insight in the crews meeting with this new land. Captain Junges journal is found together with his dead crew in a house in a fjord nearby Ny-Ålesund and has no drawings, but word. Both of these journals may be read as sources of the knowledge and understanding of the polar region. They might also unveil the ideas of how to deal with and survive under the challenges that is given. In addition one can ask if the sources can tell us more about how men describe their challenges. Can the way they expressed themselves in the journals give us an understanding of masculinity? And not least help us to create good questions of the change in the ideas of masculinities which is said to follow the change in understanding of the wilderness.